The Impact of Audit Committees on US Nonprofit Organizations’ Governance - Husam Abu-Khadra (STIE Malangkucecwara, 2020)
All public companies in the United States are required by the securities and exchange commission (SEC) to have an audit committee. Such enforcement can be attributed to high-profile corporate failures and their connections to nonexistence, ineffective or weak audit committees and governance. Despite the efforts to establish a similar argument and enforcement structure for the nonprofit sector, the internal revenue service (IRS) has not pursued legislation, and no empirical evidence has been established to support any public policy changes. This paper contributes to the literature in this field by being the first study to examine 124,980 nonprofit organizations during the period of 2010 to 2015 to test the association between governance in nonprofit organizations and audit committees. We included fifteen measures from these organizations’ IRS Form 990 filings to formulate the study variables. We found significant evidence that the existence of audit committees improves the governance scores of nonprofit organizations. Our study findings have significant implications for nonprofit executives, policy makers and any other interested parties; these findings act as preliminary evidence to support more proactive policies regarding mandatory audit committees for nonprofit organizations.